Confirmatory Virucidal Activity of Ionised Active Water S-100® on the SARS-CoV-2 Virus. (17th June 2022) - Wurtz, Nathalie; Hasni, Issam; Bancod, Audrey; La Scola, Bernard
Abstract : Ionised active water S-100® has been proposed as an original solution for use in dermocosmetics and for the treatment of wounds such as burns and atopic dermatitis. Among the mechanisms of action that are not completely understood, an antimicrobial activity would appear to be important. In the context of the COVID-19 pandemic, we assessed the inactivating efficacy of this solution on SARS-CoV-2 based on the recommendations of the NF-EN-14476+A2 standard. The tests carried out demonstrated that ionised active water S-100® 40% has a virucidal activity on SARS-CoV-2 which is at least 3.1 log after a contact time of 30 seconds and 3.5 log after two minutes at 20°C under clean conditions. Assays were also performed at 4°C and 37°C, and the results obtained are identical to those obtained at 20°C. This demonstration of the virucidal effect of ionised water against SARS-CoV-2 paves the way for the development of usage as an alternative disinfectant in SARS-CoV-2 control.